Forecastlng Yields of Pearl Millet and Sorghum in Arid Regions - Krishna, G V.S.R; Yadav, M D (Annals of Arid Zone, 2016)
Yield forecast models for pearl millet and sorghum, tile two major cereal crops of arid regions, have been developed. Yield of the pearl millet can be predicted at about 10 weeks after sowing, using the weighted rainfall, minimum temperature and eye estimates while that of the sorghum at about 11 weeks after sowing using the rainfall, maximum and minimum temperatures, average sunshine hours and eye estimates.